2011
DOI: 10.1111/j.1478-5153.2011.00436.x
|View full text |Cite
|
Sign up to set email alerts
|

Pain assessment in turning procedures for patients with invasive mechanical ventilation

Abstract: The good measurement qualities of the CPOT scale obtained during a painful procedure recommend its use in intensive care units (ICUs) for adult patients with artificial ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 27 publications
3
53
1
12
Order By: Relevance
“…Vázquez et al 39 conducted a prospective, repeatedmeasures study in a 12-bed general ICU in Spain. A total of 330 paired observations were completed in a study sample of 96 critically ill patients.…”
Section: Critical-care Pain Observation Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…Vázquez et al 39 conducted a prospective, repeatedmeasures study in a 12-bed general ICU in Spain. A total of 330 paired observations were completed in a study sample of 96 critically ill patients.…”
Section: Critical-care Pain Observation Toolmentioning
confidence: 99%
“…Patients with compromised hemodynamic status, who account for a large proportion of critically ill adults, are also at risk; these patients were often excluded in the aforementioned studies. 28,30,39 Therefore, the validity of observational pain scales in patients with hemodynamic instability needs to be further explored.…”
Section: Summary and Recommendations For Further Researchmentioning
confidence: 99%
“…33 Discriminant validation was supported, with significant increases found of 2 to 3 points in CPOT scores seen during nociceptive procedures (e.g., turning, endotracheal suctioning), as compared with CPOT scores at rest or during non-nociceptive procedures (e.g., taking noninvasive blood pressure using cuff inflation, arm wash). 16,[33][34][35]37,38 The majority of ICU nurses who used the CPOT in a research context evaluated its feasibility positively and agreed that it was quick to use, simple to understand, and easy to complete. 39 Finally, a recent implementation study of the CPOT in an ICU showed a positive influence on pain practices, with increased regular pain assessments and better use of analgesic and sedative agents postimplementation of the tool.…”
Section: Critical-care Pain Observation Toolmentioning
confidence: 99%
“…Efek samping dari penggunaan kedua obat nyeri dan obat sedatif memiliki efek buruk yang sinergis ke pasien. Tantangannya adalah memilih kombinasi obat untuk menghindari efek overdosis obat (Vazquez et al, 2011). Sementara jika tingkat sedasi tinggi dapat menyebabkan masalah seperti kecemasan, ekstubasi yang disengaja atau kerusakan fisik, serta dapat menyebabkan ketergantungan berkepanjangan pada penggunaan ventilasi mekanik (Aitken, Marshall, Elliott, & McKinley, 2009).…”
Section: Pembahasanunclassified